(untitled) (Annual of the Faculty of Philosophy in Skopje, 2022)
The security paradigm associated with challenges, risks and threats has acquired significantly new features at the threshold of the third decade of the 21st century. In that context, the geopolitical, military, economic and environmental factors that determine the security reality in the international community and countries have changed. The forces that spurred change emerged from the dynamics of the processes of internationalization and globalization, and they were a trigger for a deeper and broader analysis of security in the modern interdependent world. The complexity stems from the fact that modern security risks and dangers in many respects differ from the former risks which were unpredictable, difficult to control and determine their causes, origins and the effects they can cause. Risks and threats today vary in the form and intensity of manifestations from global pandemic to war on European soil, possible confrontation between superpowers, arms race, inequality, refugee, migrant, financial and energy crises, global climate change and cyber-attacks. It is obvious that we have created risks and dangers that no previous generation has faced. This changed security environment has increased the feeling of helplessness and the endless search for security and protection from new multimodal risks and threats. Therefore, we will analyse the classification of global risks, as well as the types of security risks faced by certain countries.